Performance of 97-elements ALPAO membrane magnetic deformable mirror in Adaptive Optics - Optical Coherence Tomography system for in vivo imaging of human retina - Zawadzki, Robert J.; Jones, Steven M.; Balderas-Mata, Sandra E.; Maliszewska, Sylwia M.; Olivier, Scot S.; Werner, John S. (Photonics Letters of Poland, 2011)
We present an evaluation of two different configurations of the ALPAO 97-actuator membrane magnetic deformable mirror for wavefront correction, using either 7 or 9 actuators across the eye pupil. These tests included monitoring of aberration correction for a human subject. This AO-sub system is part of the UC Davis high-resolution human retinal imaging adaptive optics - optical coherence tomography (AO-OCT) instrument. AO-OCT allows the three-dimensional (3D) visualization of different retinal structures in vivo with high volumetric resolution (3x3x3?m3). Full Text: PDF References: [1] R.J. Zawadzki, S. Jones, S. Olivier, M. Zhao, B. Bower, J. Izatt, S. Choi, S. Laut, and J. Werner, "Adaptive-optics optical coherence tomography for high-resolution and high-speed 3D retinal in vivo imaging", Opt. Exp. 13, 8532 (2005), [CrossRef] [2] R.J. Zawadzki, B. Cense, Y. Zhang, S.S. Choi, D.T. Miller, and J.S. Werner, "Ultrahigh-resolution optical coherence tomography with monochromatic and chromatic aberration correction", Opt. Exp. 16, 8126 (2008), [CrossRef] [3] R.J. Zawadzki, S.M. Jones, S. Pilli, S. Balderas-Mata, D. Kim, S.S. Olivier, and J.S. Werner, "Integrated adaptive optics optical coherence tomography and adaptive optics scanning laser ophthalmoscope system for simultaneous cellular resolution in vivo retinal imaging", Biomed. Opt. Exp. 2, 1674 (2011), [CrossRef] [4] J. Liang, D.R. Williams and D.T. Miller, "Supernormal vision and high-resolution retinal imaging through adaptive optics", J. Opt. Soc. Am. A 14, 2884 (1997), [CrossRef] [5] A. Roorda, F. Romero-Borja, W.J. Donnelly III, H. Queener, T.J. Hebert, and M.C.W. Campbell, "Adaptive optics scanning laser ophthalmoscopy", Opt. Exp. 10, 405 (2002), [DirectLink] D. Huang, E. A. Swanson, C.P. Lin, J.S. Schuman, W.G. Stinson, W. Chang, M.R. Flotte, K. Gregory, C.A. Puliafito, "Optical coherence tomography", Science 254, 1178 (1991). [CrossRef] W. Drexler and J.G. Fujimoto, "Optical Coherence Tomography in Ophthalmology", J. Biomed. Opt. 12, 041201 (2007). [CrossRef] [8] M. Wojtkowski, "High-speed optical coherence tomography: basics and applications", Applied Optics 49, D30 (2010), [CrossRef] D.A. Horsley, H. Park, S.P. Laut and J.S. Werner, "Characterization of a bimorph deformable mirror using stroboscopic phase-shifting interferometry", Sensors and Actuators A: Physical 134, 221 (2007). [CrossRef] J.W. Evans, R.J. Zawadzki, S.M. Jones, S.S. Olivier, and J.S. Werner, "Error budget analysis for an Adaptive Optics Optical Coherence Tomography System", Opt. Exp. 17, 13768 (2009), [CrossRef] N. Doble, D.T. Miller, G. Yoon, and D.R. Williams, "Requirements for discrete actuator and segmented wavefront correctors for aberration compensation in two large populations of human eyes", Appl. Opt. 46, 4501 (2007), [CrossRef] N. Devaney, E. Dalimier, T. Farrell, D. Coburn, R. Mackey, D. Mackey, F. Laurent, E. Daly, and C. Dainty, "Correction of ocular and atmospheric wavefronts: a comparison of the performance of various deformable mirrors", Appl. Opt. 47, 6550 [CrossRef]